2022
DOI: 10.3889/oamjms.2022.8698
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Steeped White Tea, Black Tea, and Green Tea against Streptococcus mutans and Plaque Accumulation

Abstract: BACKGROUND: Tea is the most consumed beverage in the world after water. Tea (Camellia sinensis) is native to Southeast Asia and is now available in more than 30 countries. Tea has various health properties. Tea has an active component, namely catechins, which can inhibit the growth of Streptococcus mutans as a component of dental plaque formation. AIM: This study aims to determine the antibacterial effect of steeped white tea, black tea, and green tea on S. mutans and plaque accumulation. METHODS: The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Dental plaque contains highly organized microbial communities that adhere to the surface of hard dental tissues and is a major cause of various oral and pharyngeal diseases (Digel et al, 2020). In a clinical study, mouth rinsing with steeped 2.5% white tea steeped twice daily for four days significantly improved the plaque index, indicating a reduction in plaque accumulation on teeth (Damhuji et al, 2022). A similar study reported that white tea mouthwash was a potent antiplaque agent when used for 10 d, although less effective than chlorhexidine, a gold standard for plaque (Nagar et al, 2018).…”
Section: Oral Healthmentioning
confidence: 99%
“…Dental plaque contains highly organized microbial communities that adhere to the surface of hard dental tissues and is a major cause of various oral and pharyngeal diseases (Digel et al, 2020). In a clinical study, mouth rinsing with steeped 2.5% white tea steeped twice daily for four days significantly improved the plaque index, indicating a reduction in plaque accumulation on teeth (Damhuji et al, 2022). A similar study reported that white tea mouthwash was a potent antiplaque agent when used for 10 d, although less effective than chlorhexidine, a gold standard for plaque (Nagar et al, 2018).…”
Section: Oral Healthmentioning
confidence: 99%
“…Dibalik kegemaran masyarakat tentang mengonsumsi teh hitam dan efek menguntungkan teh sebagai antibakteri, ternyata teh hitam mengandung senyawa tanin yang dapat mengakibatkan perubahan warna pada gigi (diskolorasi gigi). [4][5][6] Pasien yang mengalami diskolorasi gigi akan mencari cara untuk mengembalikan kembali warna gigi yang lebih putih dan cerah seperti semula; salah satu cara yang paling umum dilakukan yaitu pemutihan gigi (bleaching). Bleaching merupakan teknik memutihkan yang dilakukan oleh dokter gigi, dengan harga yang cenderung mahal sehingga pasien yang mengalami diskolorasi gigi dengan tingkat ekonomi yang relatif rendah akan mencari bahan alami sebagai alternatif untuk mengembalikan warna gigi yang cerah.…”
Section: Pendahuluanunclassified